Análisis Doctrinario del Ciberbullying como delito informático en el Derecho Penal Ecuatoriano - Jaramillo Castro, Daniela Sthefanía (2019)
The present research work developed under the title of "Doctrinal analysis of cyberbullying as a cybercrime within Ecuadorian Criminal Law" arises from the legal vacuum that exists in the Organic Comprehensive Criminal Code of our country, with respect to the lack of typing antisocial criminal behaviors that arise through electronic means, a phenomenon better known as "cyberbullying" or "cyberbullying." It constitutes a criminal figure that provokes changes in people in human behavior, where not only social relationships suffer damage in the personal sphere, but also collaterally causes both physical and emotional injuries to people around our environment. The State as a legal institution is the one who takes care that the respect and protection of the rights established in the Ecuadorian legal bodies is guaranteed, it is necessary to add importance to the fundamental rights in this subject, since they are inherent to all human beings, being ourselves responsible for our ability to act. However, for these fundamental rights to be considered as such, they must imply a sanction whose responsibility rests with the legislators within the Legislative Function. This research will be developed from the doctrinal study of the different forms of communication and its elements that have been evolving in a fleeting and unnoticed manner, pointing out in the beginning the scarcity and difficulty of the methods that were previously used to achieve good communication between peoples , with the passing of the years, the virtual dependency where social networks come to play a 5 leading role in the lives of human beings, because some of them often use cyberspace as a refuge to hide their true identity. identity and thus criminalize through electronic means, criminal behaviors known as cyberbullying. In order to fully comply with the objectives proposed in this research project, an in-depth analysis was carried out through the compilation of legal and doctrinal bibliographic resources, in the same way the study of the different legislations established in other countries was taken into account. Criminal codes cyberbullying is a computer crime with its respective penalty. The application of methods and techniques such as the survey and interview, aimed at legal professionals, will allow to establish well-founded criteria that determine whether or not there is a need for a reform proposal oriented towards social and cultural reality, taking into account the legislative needs of our country, which guarantees a correct administration of justice.